Effect of flippits versus virtual reality on pain, fear, and satisfaction during phlebotomy among children - Eman Wardany Abdelaal Mohamed; Heba Ibrahem Mohamed (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the effect of flippits versus virtual reality on pain, fear and satisfaction among children during phlebotomy. Method: The quasi-experiential study was conducted at the Paediatric Medical Department of Kafrelsheikh University Hospital, Egypt, from November 2021 to April 2022, and comprised children of either gender aged 6-12 years. The subjects were randomised into flippits group A, virtual reality group B and control group C in which only traditional care was provided. Data was collected using a structured interview, Wong-Baker Faces Pain Rating Scale, Children’s Fear Scale, and Blood Specimen Collection Satisfaction Evaluation Scale. Data was analysed using SPSS 20. Results: Of the 120 children, 40(33.3%) were in each of the three groups. There were 21(52.5%) boys and 19(47.5%) girls in group A with mean age 8.2±1.6 years, 22(55%) boys and 18(45%) girls in group B with mean age 7.8±1.7 years, and 27(67.5%) boys and 13(32.5%) girls in group C with mean age 7.9±1.9 years (p>0.05). Mean pain and fear scores were significantly lower and mean satisfaction score was higher in groups A and B than group C (p<0.05). There was no significant difference in the mean pain scores of group A and group B (p>0.05). Conclusion: Flippits and virtual reality interventions had a positive effect on pain, fear and satisfaction levels in children during phlebotomy. Keywords: Phlebotomy, Pain, Fippits, Fear, Children